Happy Easter, Davy! - Weninger, Brigitte (North-South Books, 2014)
Davy's big brother has just heard about the Easter Bunny who brings human children presents and colored eggs. The Rabbit children immediately decide to go find the Easter Bunny and ask him to bring them gifts too.